"A Review: Biomechanical Substitutions during Pregnancy and Application of Orthoses" - Bin Yar, Usama (Journal of University Medical & Dental College, 2022)
Pregnancy-related biomechanical adjustments might result in alterations in gait patterns. These modifications can change spine balance, curvature, and ambulatory patterns during pregnancy by influencing important parts of the body. The musculoskeletal system’s responses to structural substitutions during pregnancy are not entirely apprehended. As a result, the primary goal of this review is to gather the important biomechanical replacements that affect gait patterns during pregnancy. Furthermore, these biomechanical alterations are investigated in-depth, and several orthotic interventions are proposed to combat these changes; nevertheless, it has yet to be determined whether or not orthoses are advantageous during pregnancy. In the light of literature, some pieces of evidence are included, but suitable guidelines are lacking to gain a better grasp of pregnancy biomechanical changes and the effect of orthoses.